2014
DOI: 10.5216/ree.v16i1.20991
|View full text |Cite
|
Sign up to set email alerts
|

Dor, alterações fisiológicas e analgesia nos pacientes submetidos a cirurgias de médio porte

Abstract: Dor, alterações fisiológicas e analgesia nos pacientes submetidos a cirurgias de médio portePain, physiological alterations and analgesia in patients submitted to medium-sized surgeries Dolor, alteraciones fisiológicas y analgesia en pacientes sometidos a cirugías de mediana complejidad

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 13 publications
0
5
0
7
Order By: Relevance
“…9 It is essential for the effective evaluation of pain, the participation of the Nursing team, who develops daily activities at all shifts and, thus, is able to observe more fully the complaints and alterations presented by the patient to provide comprehensive, holistic and quality care. 6,10 Through an adequate evaluation concomitant to the measurement of pain, it is possible to establish efficient management and control with the formation of an individual plan that overcomes the damages caused by the pain problem. Therefore, the use of scales facilitates the assessment of pain and strengthens the contact between the professional and the patient.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…9 It is essential for the effective evaluation of pain, the participation of the Nursing team, who develops daily activities at all shifts and, thus, is able to observe more fully the complaints and alterations presented by the patient to provide comprehensive, holistic and quality care. 6,10 Through an adequate evaluation concomitant to the measurement of pain, it is possible to establish efficient management and control with the formation of an individual plan that overcomes the damages caused by the pain problem. Therefore, the use of scales facilitates the assessment of pain and strengthens the contact between the professional and the patient.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the use of scales facilitates the assessment of pain and strengthens the contact between the professional and the patient. 6 In a study carried out with 100 patients from a ward of a university hospital in the south of Minas Gerais, where there was permanent education and the applicability of a numerical pain scale, the evaluation of postoperative pain was carried out in an effective way, since 90 patients (90%) considered the excellent care and treatment of pain and ten patients (10%) evaluated the care as good.³ It is demonstrated that the main intervention performed for pain control, according to the DSC, is the prescribed medication, which corroborated a study carried out in Bogotá where nursing professionals use the prescribed medications as first choice and secondarily nonpharmacological interventions due to absence of standardization for both postoperative pain assessment and management. [14][15] It was proven, in another study conducted with physicians and nurses on their knowledge about this sign, that all (100%) had mastered pharmacological practice in pain relief, but in comparison to non-drug practices, only 37% 50%, respectively, reported having knowledge about distraction and relaxation practices in their improvement.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dentre as condições que podem afetar a recuperação do indivíduo, a dor merece destaque especial 7,13 . O controle da dor no pósoperatório evita sofrimento e proporciona maior satisfação do paciente com o atendimento e reduz os custos relacionados a possíveis complicações, que determinam maiores períodos de internação 14 .…”
Section: Discussionunclassified